KNOWLEDGE, ATTITUDES, AND PRACTICES REGARDING HPV PREVENTION FOR CERVICAL CANCER AMONG WOMEN AGED 15-49 YEARS IN AN GIANG PROVINCE (Vietnam Journal of Community Medicine, 2026)
Objectives: To assess the current status of knowledge, attitudes, and practices related to HPV prevention for cervical cancer and to identify associated factors among women aged 15-49 years in An Giang province.Subjects and methods: An analytical cross-sectional study was conducted by interviewing 260 women aged 15-49 years who attended Giong Rieng Medical Center, An Giang province.Results: The proportions of women with adequate knowledge, positive attitudes and appropriate practices were 67.3%, 80% and 78.1%, including people with an education level above high school and those who received information from healthcare workers had the highest levels of correct knowledge, with statistically significant differences (p < 0.05). 80% of participants demonstrated positive attitudes toward HPV prevention. Age, educational level, occupation and economic status were significantly associated with attitudes toward HPV prevention (p < 0.05). Correct preventive practices against HPV infection were more common among salaried workers 40.5% (p < 0.05), having an education level above high school 100% (p < 0.01) and those who received information from healthcare workers 94.3% (p < 0.01).Conclusion: The study indicates that the levels of knowledge, attitudes, and practices among the participants were relatively good. Educational level, economic status and access to health information were important factors influencing women’s knowledge and positive attitudes toward HPV prevention in cervical cancer. Coordinated efforts to improve socioeconomic conditions and strengthen health education and communication are necessary to enhance knowledge, attitudes, and preventive practices among women of reproductive age.
Keywords: Cervical cancer, knowledge, attitude, practice, HPV, HPV vaccine, prevention, associated factors.